Flexible Planar‐Integrated Micro‐Supercapacitors from Electrochemically Exfoliated Graphene as Advanced Electrodes Prepared by Flash Foam–Assisted Stamp Technique on Paper. Issue 11 (5th September 2019) - Shi, Qingling; Xiang, Yangjun; Ji, Guanghan; Wang, Debo; Wang, Xiangfu; Xu, Rongqing; Jiang, Li; Yu, Ying; Zhao, Jiang
Abstract : One of the key challenges of integrated energy storage devices is to develop a simple, low‐cost, and environmental‐friendly planar patterning technology. Herein, an ingenious and feasible laser‐engraved flash foam–assisted stamp technique of preparing flexible paper‐based planar‐integrated micro‐supercapacitors based on interdigital electrodes of self‐depositing electrochemically exfoliated graphene is proposed. The as‐synthesized flexible paper‐based planar‐integrated graphene micro‐supercapacitors exhibit excellent electrochemical performances with a remarkable area‐specific capacitance of 3.1 mF cm −2, and an excellent cycling stability in that capacitance retention reaches 95.8% even after 10 000 cycles. Furthermore, the paper‐based graphene micro‐supercapacitors are bent at different angles without significant electrochemical performance loss, and thus have outstanding mechanical flexibility. Therefore, such flexible paper‐based planar‐integrated graphene micro‐supercapacitors are expected to be applied in flexible wearable and portable electronics. Abstract : Flexible planar‐integrated micro‐supercapacitors from electrochemically exfoliated graphene as advanced electrodes are prepared by a flash foam–assisted stamp technique on paper.